Understanding Tactile Characteristics of Natural Yarn and Fabric Through Sensory Descriptive Analysis - Aussama Soontrunnarudrungsri; Kunalai Ploydanai; Thanyachol Apipatpapha; Rungsima Chollakup; Pithalai Lekutai (Journal of Natural Fibers)
This study investigates the tactile properties of natural yarns and fabrics through sensory descriptive analysis, supported by Principal Component Analysis (PCA) and hierarchical cluster analysis to identify clusters with similar sensory profiles. Hemp/Cotton yarns (garabo spinning), Eri silk/Mulberry silk yarns (open-end spinning), and Brown Cotton/Cotton yarns (hand spinning) exhibited superior softness and smoothness. The spinning method emerged as the key factor in shaping tactile profiles; hand spinning, garabo spinning, and slub yarn techniques produced softer and fluffier textures, while ring spinning and open-end spinning yielded tighter, less textured fabrics. Correlation analysis further highlighted the influence of physical properties on tactile characteristics, including the positive relationship between twist number and both tightness and grittiness. These findings emphasize the critical role of spinning methods, fabric characteristics, and physical properties in determining the tactile qualities of sustainable textiles, offering valuable insights for material optimization in the textile industry.